Calpain‐activated mTORC2/Akt pathway mediates airway smooth muscle remodelling in asthma. Issue 2 (14th October 2016) - Rao, S.‐S.; Mu, Q.; Zeng, Y.; Cai, P.‐C.; Liu, F.; Yang, J.; Xia, Y.; Zhang, Q.; Song, L.‐J.; Zhou, L.‐L.; Li, F.‐Z.; Lin, Y.‐X.; et al.
Summary: Background: Allergic asthma is characterized by inflammation and airway remodelling. Airway remodelling with excessive deposition of extracellular matrix (ECM) and larger smooth muscle mass are correlated with increased airway responsiveness and asthma severity. Calpain is a family of calcium‐dependent endopeptidases, which plays an important role in ECM remodelling. However, the role of calpain in airway smooth muscle remodelling remains unknown. Objective: To investigate the role of calpain in asthmatic airway remodelling as well as the underlying mechanism. Methods: The mouse asthma model was made by ovalbumin sensitization and challenge. Calpain conditional knockout mice were studied in the model. Airway smooth muscle cells (ASMCs) were isolated from smooth muscle bundles in airway of rats. Cytokines IL‐4, IL‐5, TNF‐α, and TGF‐β1, and serum from patients with asthma were selected to treated ASMCs. Collagen‐I synthesis, cell proliferation, and phosphorylation of Akt in ASMCs were analysed. Results: Inhibition of calpain using calpain knockout mice attenuated airway smooth muscle remodelling in mouse asthma models. Cytokines IL‐4, IL‐5, TNF‐α, and TGF‐β1, and serum from patients with asthma increased collagen‐I synthesis, cell proliferation, and phosphorylation of Akt in ASMCs, which were blocked by the calpain inhibitor MDL28170. Moreover, MDL28170 reduced cytokine‐induced increases in Rictor protein, which is the most important component of mammalian target of rapamycin complex 2 (mTORC2). Blockage of the mTORC2 signal pathway prevented cytokine‐induced phosphorylation of Akt, collagen‐I synthesis, and cell proliferation of ASMCs and attenuated airway smooth muscle remodelling in mouse asthma models. Conclusions and Clinical Relevance: Our results indicate that calpain mediates cytokine‐induced collagen‐I synthesis and proliferation of ASMCs via the mTORC2/Akt signalling pathway, thereby regulating airway smooth muscle remodelling in asthma.